The Effect of Local Wisdom-based Material on Student’s Reading Ability - Fatmawaty, Riryn; Farih, Abdullah; Ningsih, Wahyu Hidayati (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
The problem faced by human beings is the inability to live together harmoniously with others. This problem can be solved by learning and adapting local wisdom in every situation, this confirms that local wisdom is one of the crucial things to teach in schools. Local wisdom is very important because it contains moral values. The aim of this study is to analyze the material based on local wisdom has an effect on students' reading ability. The research design of this study is a quasi-experimental research with a non-equivalent control group design. This study was conducted on students of 12 grade senior high school, the sample used consisted of experimental and control classes each with 22 students, and the instruments used are test and non-test. The results of inferential statistical analysis using the paired sample t-test showed that the average value of the results of the experimental class's pretest reading ability was 67.77 while for the post-test experiment it was 85.55. In addition, the results of the questionnaire showed that there were about 89% of students gave a positive response, so it can be concluded that the application of material based on local wisdom has an effect on students' reading ability.